2015
DOI: 10.1038/leu.2015.328
|View full text |Cite
|
Sign up to set email alerts
|

Highly recurrent mutations of SGK1, DUSP2 and JUNB in nodular lymphocyte predominant Hodgkin lymphoma

Abstract: Nodular lymphocyte predominant Hodgkin lymphoma (NLPHL)-a subtype of Hodgkin lymphoma (HL)-is characterized by a low content of tumor cells, the lymphocyte predominant (LP) cells. Transformation into diffuse large B-cell lymphoma (DLBCL) occurs in about 10% of patients. We performed whole-genome mutation analysis of the DLBCL components from two composite lymphomas consisting of clonally related NLPHL and DLBCL as a means to identify candidate tumor suppressor genes and oncogenes in NLPHL. The analysis of LP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 54 publications
4
72
0
Order By: Relevance
“…Similar to AKT isoforms, SGK1 does not appear to be frequently mutated in human tumors, although a recent study has found frequent SGK1 mutations (approximately 50% of samples) in nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) (Hartmann et al, 2016). The functional significance of these alterations remains anyway to be defined.…”
Section: Sgk1 and Cancermentioning
confidence: 99%
“…Similar to AKT isoforms, SGK1 does not appear to be frequently mutated in human tumors, although a recent study has found frequent SGK1 mutations (approximately 50% of samples) in nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) (Hartmann et al, 2016). The functional significance of these alterations remains anyway to be defined.…”
Section: Sgk1 and Cancermentioning
confidence: 99%
“…Genome-wide, this identified 649 somatic eQTL (FDR ≤ 5%; Supplementary Table 4) associated with 567 unique regions. Among these, 11 somatic eQTL were explained by mutational burdens in exons or introns, including genes with known roles in the pathogenesis of specific cancers such as CDK12 in ovarian cancer 29,30 , PI4KA in hepatocellular carcinoma 31 , IRF4 in leukemia 32 , AICDA in skin melanoma 33 , C11orf73 in clear cell renal cancer 34 and BCL2 and SGK1 in lymphoma 35 , Extended Data Figure 12a-g). The majority of eGenes (68.4%) involved associations with flanking non-coding intervals (272 intergenic, 172 intronic regions, Figure 2d), and were due to mutations observed in multiple cancers (Extended Data Figure 13a, Supplementary Table 4).…”
Section: Somatic Cis Eqtl Mapping Reveals Widespread Associations Witmentioning
confidence: 99%
“…Genome-wide, this identified 649 somatic eQTL (FDR ≤ 5%; Table S6 ) in 567 genomic regions. Among these, 11 somatic eQTL were explained by the mutational burden in exons or introns, including genes with known roles in the pathogenesis of specific cancers such as CDK12 in ovarian cancer (Bajrami et al 2013;Ekumi et al 2015) , PI4KA in hepatocellular carcinoma (Ilboudo et al 2014) , IRF4 in leukemia (Havelange et al 2011) , AICDA in skin melanoma (Nonaka et al 2016) , C11orf73 in clear cell renal cancer (Bhalla et al 2017) and BCL2 and SGK1 in lymphoma (Weinhold et al 2014 ;Hartmann et al 2016 , Fig. S12 A-G ).…”
Section: Somatic Eqtl Mapping Reveals Widespread Associations With Nomentioning
confidence: 99%